Protective effects of Quercus acuta Thunb. fruit extract against UVB-induced photoaging through ERK/AP-1 signaling modulation in human keratinocytes - Ji-Ae Hong; Donghyuk Bae; Kyo-Nyeo Oh; Dool-Ri Oh; Yujin Kim; Yonguk Kim; So Jeong Im; Eun-jin Choi; Seul-gi Lee; Moonjong Kim; Changsik Jeong; Chul Yung Choi (BMC, 2022)
Abstract Background Quercus acuta Thunb. (Fagaceae) or Japanese evergreen oak is cultivated as an ornamental plant in South Korea, China, Japan, and Taiwan and used in traditional medicine. The acorn or fruit of Quercus acuta Thunb. (QAF) is the main ingredient of acorn jelly, a traditional food in Korea. Its leaf was recently shown to have potent xanthine oxidase inhibitory and anti-hyperuricemic activities; however, there have been no studies on the biological activity of QAF extracts. Solar ultraviolet light triggers photoaging of the skin, which increases the production of reactive oxygen species (ROS) and expression of matrix metalloproteinase (MMPs), and destroys collagen fibers, consequently inducing wrinkle formation. The aim of this study was to investigate the effect of water extracts of QAF against UVB-induced skin photoaging and to elucidate the underlying molecular mechanisms in human keratinocytes (HaCaT). Methods In this study, we used HPLC to identify the major active components of QAF water extracts. Anti-photoaging effects of QAF extracts were evaluated by analyzing ROS procollagen type I in UVB-irradiated HaCaT keratinocytes. Antiradical activity was determined using 2,2-diphenyl-1-picrylhydrazyl and 2,20-azino-bis (3-ethylbenzothiazoline-6-sulphonic acid) assays. The expression of MMP-1 was tested by western blotting and ELISA kits. QAF effects on phosphorylation of the MAPK (p38, JNK, and ERK) pathway and transcription factor AP-1, which enhances the expression of MMPs, were analyzed by western blots. Results We identified two major active components in QAF water extracts, gallotannic acid and ellagic acid. The QAF aqueous extracts recovered UVB-induced cell toxicity and reduced oxidative stress by inhibiting intracellular ROS generation in HaCaT cells. QAF rescued UVB-induced collagen degradation by suppressing MMP-1 expression. The anti-photoaging activities of QAF were associated with the inhibition of UVB-induced phosphorylation of extracellular signal-regulated kinase (ERK) and activator protein 1 (AP-1). Our findings indicated that QAF prevents UVB-induced skin damage due to collagen degradation and MMP-1 activation via inactivation of the ERK/AP-1 signaling pathway. Overall, this study strongly suggests that QAF exerts anti-skin-aging effects and is a potential natural biomaterial that inhibits UVB-induced photoaging. Conclusion These results show that QAF water extract effectively prevents skin photoaging by enhancing collagen deposition and inhibiting MMP-1 via the ERK/AP-1 signaling pathway.